Hubungan Pola Asuh Orang Tua dengan Perilaku Sulit Makan Pada Anak Usia Prasekolah: Literature Review: Hubungan Pola Asuh Orang Tua dengan Perilaku Sulit Makan Pada Anak Usia Prasekolah: Literature Review - Siti Dewi Rahmayanti; Nunung Nurjanah; Yosie Dian Anggraeni (JURNAL KESEHATAN KARTIKA, 2022)
ABSTRACT THE CORRELATION OF PARENTING STYLE WITH DIFFICUTLY EATING BEHAVIOR: LITERATURE REVIEW Background: Preschool children are children aged 3-6 years. At this time children experience a significant process of growth and development in psychosocial, biological, cognitive and spiritual aspects. Based on research conducted in New Zealand, it was reported that 24% of respondents complained of having difficulty eating problems at the age of three and 18% of them continued until the age of five (UNICEF, 2018). The causes of eating difficulties in children are very diverse, one of which is psychological factors. Parenting style can determine the occurrence of psychological disorders in children which can lead to eating disorders so that it has an impact on the process of growth and development. Objectives: To identify the relationship between parenting patterns and difficult eating behavior in preschool-aged children. Method: This study uses a literature review method, obtained 5 research journal articles through a search of academic databases according to the inclusion criteria. Test based on JBI Critical Apparition Checklist For Analytical Cross Sectional Study. Stages of literature selection using PRISMA. Results: This study shows that there is a relationship between parental parenting and difficult eating behavior. Conclusion: Based on a literature review of the five articles, it shows that the majority of parents who apply democratic parenting are less likely to have difficult eating behaviors and parents who apply authoritarian and permissive parenting are more likely to have difficult eating behaviors. The results of the literature review are expected to be the development of basic knowledge in the development of knowledge related to parenting style and difficult eating behavior in children. Keywords: Preschool, Difficult eating behavior, Parenting Style Literature: 22, 2011-2021